Bathing suit ichthyosis - Sahana M Srinivas; Rachana Shekar; Ravi Hiremagalore (Wolters Kluwer Medknow Publications, 2018)
Bathing suit ichthyosis (BSI) is a rare, autosomal recessive form of congenital ichthyosis. The phenotypic expression of this unique form of ichthyosis is limited to the involvement of bathing suit area owing to the temperature-sensitive mutation of transglutaminase 1 gene. Lack of Indian literature of this rare condition made us to report three cases of BSI in healthy female children who presented with ichthyotic scales on the trunk since birth with sparing of extremities.